Pengaruh Analisa Uang Beredar Dan Nilai Waktu Uang Terhadap Keputusan Investasi Surat Berharga - Febrian Febrian; Sumriyah Sumriyah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The development of the era of economic and financial digitalization is developing so rapidly, that the purpose of this writing is to find out how the relationship between the time value of the rupiah influences over time. In addition, of course, the development of the era of economic and financial digitalization has had an impact on Indonesia's progress. Often companies have confusion in investing in securities, in this article the author wants to further discuss the role of the money supply and the time value of money in investing in securities. Of course, in making an investment decision, a company must carry out financial analysis related to stocks, bonds and capital markets. The method used is qualitative by collecting, analyzing and processing data from accurate and reliable sources such as books, journals and government websites. The results of this study indicate that by analyzing the money supply and the time value of money, it will influence companies in making investment decisions on securities using fundamental analysis.